Why we should not ‘just use age’ for COVID-19 vaccine prioritisation - Smith, Maxwell J. (Journal of medical ethics, 2022)
Older age is one of the greatest risk factors for severe outcomes from COVID-19. If we believe it is important to use limited supplies of COVID-19 vaccines to protect the most vulnerable and prevent deaths, then available doses should be allocated with significant priority to older adults. Yet, we should resist the conclusion that age should be the sole criterion for COVID-19 vaccine prioritisation or that no younger populations (eg, those under the age of 60) should be prioritised until all older adults have been vaccinated. This article examines arguments that are commonly presented to abandon ‘complex’ vaccine prioritisation schemes in favour of ‘just using age’ (eg, prioritising those 80 years of age and older and then decreasing in a 5-year age bands until the entire population has had the opportunity to be vaccinated), and articulates the ethical reasons why these arguments are not persuasive.